EKSISTENSI DAN PERANAN PEREMPUAN DALAM RANAH POLITIK DI INDONESIA - Toguan Rambe (IAIN Padangsidimpuan, 2022)
This paper is the result of research related to the existence and political role of women in Indonesia, since the reformation, the existence and political role of women in making decisions on an important matter related to gaining power. From the existence of women on the other hand, it can be traced that before the birth of the Unitary Republic of Indonesia, it was difficult for women to have a role in the political context. Politics substantially has the meaning of power, authority (power) and decision-making in a very broad scope, to find out the extent of the political role of women in Indonesia, this research was carried out by tracing various kinds of literary sources or various existing research results with the aim of providing new perspectives on the issues raised. So this type of research is library research or literature study that is tracing and analyzing various literature. The results of this study indicate that in practice women's political representation in parliament is still below the 30% quota target. Another problem lies in the ideological and psychological problems that women will face when they enter the world of politics, including gender ideology and cultural issues as well as established social constructions.Tulisan ini merupakan hasil penelitian terkait eksistensi dan peranan poltik perempuan di Indonesia, sejak reformasi, eksistensi dan peranan politik perempuan dalam pengambilan kepustusan suatu hal penting terkait memperoleh kekuasaan. eksistensi perempuan pada sisi yang lain, dapat dilelusuri bahwa sebekum lahirnya NKRI, perempun susah memiliki peranan dalam konteks politik. Politik secara subsatansial memliki makna kekuasaan, kewenangan (power) serta pengambilan putusan dalam ruang lingkup yang begitu luas, untuk mengatahui sejauh mana peranan politik perempuan di Indonesia maka penelitian ini dilakukakan melalui menelususri berbagai macam sumber literatur atau berbagai hasil penelitian yang sudah ada dengan maksud memberikan perspektif baru terkait isu yang diangkat. Maka jenis penelitian ini yakni library research atau studi kepustakaan yang bersifat menelusuri serta menganalisa dari bermacam literatur. Hasil penelitian ini menunjukkan bahwa dalam praktiknya representasi politik perempuan di parlemen masih di bawah target kuota 30%. Problem yang lian terdapat pada masalah ideologis dan psikologis yang akan dihadapi perempuan Ketika masuk dalam dunia politik, antara lain ideologi gender dan maslah-masalah kultural maupun knstruksi sosial yang sudah mapan.